Physico-chemical Characteristics of the Soils of the Ram Nagar Region of Uttaranchal (India) - Kumar Pandey, Pramod; Pant, C.S.; Mehta, S.P.S. (Asian Journal of Chemistry, 2010)
Organic carbon and organic matter contents in the soils of Ram Nagar region of Uttaranchal (India) were estimated. The results have been discussed.